The Sccs-r Model: Parenting Challenges in Families of Children with Autism - Hazlina Abdullah; Nursyuhada' Ab. Wahab; Dini Farhana Baharudin; Zarina Ashikin Zakaria; Rahimah Saimin; Myra Aidrin Mohd Ali; Norhana Abdullah (ResearchTrentz, 2024)
Indexed by ERA